Effects of long‐term simulated microgravity on liver metabolism in rhesus macaques. Issue 10 (7th September 2022) - Zong, Beibei; Wang, Yujia; Wang, Jingyi; Zhang, Peng; Kan, Guanghan; Li, Mingyang; Feng, Juan; Wang, Yifan; Chen, Xiaoping; Jin, Rong; Ge, Qing
Abstract: The liver is an essential multifunctional organ and constantly communicates with nearly all the tissues in the body. Spaceflight or simulated microgravity has a significant impact on the livers of rodent models, including lipid accumulation and inflammatory cell infiltration. Whether similar liver lipotoxicity could occur in humans is not known, even though altered circulating cholesterol profile has been reported in astronauts. Using a 42‐day head‐down bed rest (HDBR) model in rhesus macaques, the present study investigated whether simulated microgravity alters the liver of non‐human primates at the transcriptome and metabolome levels. Its association with stress and intestinal changes was also explored. Compared to the controls, the HDBR monkeys showed mild liver injury, elevated ANGPTL3 level in the plasma, and accumulation of fat vacuoles and inflammatory cells in the liver. Altered transcriptome signatures with up‐regulation of genes in lipid metabolisms and down‐regulation of genes in innate immune defense were also found in HDBR group‐derived liver samples. The metabolic profiling of the liver revealed mildly disturbed fatty acid metabolism in the liver of HDBR monkeys. The intestinal dysbiosis, its associated endotoxemia and changes in the composition of bile acids, and elevated stress hormone in HDBR monkeys may contribute to the altered lipid metabolisms in the liver. These data indicate that liver metabolic functions and gut‐liver axis should be closely monitored in prolonged spaceflight to facilitate strategy design to improve and maintain metabolic homeostasis.